An evaluation of the resistance training programmes in an elite soccer academy and it`s effects on the development of isometric strength - Brownlee, T.; O'Boyle, A.; Morgans, R.; Morton, J.; Erskine, R.; Drust, B. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
INTRODUCTION: Muscular strength is a desirable attribute in soccer players of all ages. The aim of this study was to evaluate the training completed by English Premier League soccer players in an academy over an 8-week period and to determine whether such training increased isometric strength compared to a control group. METHODS: Training for 184 elite soccer players from under 9 (U9) to under 21 (U21) was recorded over an 8-wk period. Data was examined to establish distribution of training time in soccer training, matches, nonresistance training athletic development activities and resistance training. From that group 155 elite and 93 control participants completed two sometric mid-thigh pull tests 8-wks apart. Isometric strength was expressed as both absolute and allometrically scaled (force * body mass 0.66). RESULTS: Total training time progressively increased between the U9 (268 ± 25 min/wk) and U14 (477 ± 19 min/wk) age groups with only a small proportion of training time (3 ± 18%) consisting of training focussed on solely improving physical attributes. Total training time was then subsequently reduced from the U14 to the U15 (266 ± 77 min/wk) age groups, with no differences in training duration for any groups between U15 and U21 (P > 0.05). When the U15 to U21 squads (the only players who completed resistance training) were compared no difference in session duration was observed (P > 0.05). No main effect for peak isometric force (PF) between elite (1617.10 ± 611.15 N) and control (1535.69 ± 624.83 N) groups was present (P = 0.087). For allometrically scaled force (RF) a main effect was noted with the elite cohort (118.29 ± 21.96 N) being stronger than controls (109.69 ± 27.91 N) though no interaction between group and maturity status was observed (P = 0.167). Following 8 weeks of training no changes were seen in either group for PF (at 8 wk elite group 1580.12 ± 632.55 N; control group 1496.38 ± 555.51 N) or RF (elite group at 8 wk, 119.12 ± 23.43 N; control group at 8 wk, 110.89 ± 25.75 N) (P > 0.05). DISCUSSION: These data examine training practices and isometric strength throughout an English Premier League soccer academy compared with a matched control group. They suggest that training practices evaluated here do not elicit increases in isometric strength. This is likely a result of the focus of training time on technical development. This data can provide practitioners with baseline isometric strength data and training data for comparisons across teams